SISTEM PROTEKSI GENERATOR DENGAN TAHANAN TINGGI PADA PLTU LABUHAN ANGIN TERHADAP GANGGUAN SATU FASA KE BUMI - Rinna Hariyati; Heri Suyanto; Marisa Dosma Sitanggang (Sekolah Tinggi Teknik - PLN, 2016)
High resistance grounding one of the ways ptotection generator for the single phase earth fault. High resistance grounding utilizes a distribution transformer with a primary voltage rating greater than or equal to the line to neutral voltage rating of the generator. The distribution transformer should have sufficient overvoltage capability so that it does not saturate on single line to ground faults with the generator operated at 105% of rated voltage. The power dissipated in resistor is approximately equal to the reactive volt-amperes of the zero sequence capasitive reactance of the stator windings. For High resistance grounding to be effective, the size of resistor must be carefully selected for each system. IEEE Standard C37.101 provides a detailed example of how to determine the size of the ground resistor to meet the requirements cited above, as well as calculate the resulting ground currents and voltages.